Failure to Extend Epidural Labor Analgesia for Cesarean Delivery Anesthesia: A Focused Review. (November 2016) - Mankowitz, Suzanne K. W.; Gonzalez Fiol, Antonio; Smiley, Richard
Abstract : Extension of epidural labor analgesia for cesarean delivery anesthesia may fail. There are a number of factors associated with labor epidural catheter failure. This focused review discusses these associations and anesthetic options when faced with inadequate surgical epidural anesthesia for cesarean delivery. Abstract : Published ahead of print August 12, 2016.